Adaptasi dan Formasi Liturgi dalam Ekaristi Bersama Anak di Paroki St. Mikael Nita - Marianus Ronaldo Tiba; Alexandro Putra Bei; Daniel Seti Hali Tolang (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This research explores the adaptation and formation of liturgy in the celebration of the Eucharist with children in the Parish of Nita, with the aim of understanding how liturgy can be an effective means of faith education in shaping religious, liturgical and social values that are important for the development of their Christian character. Using a qualitative descriptive approach, data was collected through interviews, direct observation and literature review. The findings show that celebrating the Eucharist with children requires various contextual adaptations, such as easily understood gestures, relevant visual symbols, selection of age-appropriate liturgical music, and active participation of children through liturgical roles. These adaptations are designed to enhance children's participation without compromising the essence of the sacredness of the Eucharist. In addition, the role of adults as companions, including parents, priests and catechists, is crucial in guiding children to understand the deeper meaning of each part of the liturgy, training them to create a conducive atmosphere for the celebration and, most importantly, providing a living example of faith. The research also confirmed that ongoing liturgical formation is an integral part of children's faith formation, which is understood as an evolving process that requires serious attention from the Church. This formation aims to enable children to understand and live the Eucharist as the mystery of Christ's sacrifice for human salvation. The results of this study provide a solid basis for the future development of liturgical adaptation and formation that encourages the active participation of children, strengthens their faith and guides them towards a more meaningful Christian life.